Serious leisure and successful aging among elderly air volleyball players: examining the mediating role of social support and flow experience - Wang, Jingzhong; Tian, Haibo (Frontiers in Psychology, 2024)
Previous literature has demonstrated that engagement in serious leisure (SL) is associated with subjective well-being among older adults, while the relationship between successful aging (SA) and SL remains unexplored. This study aims to investigated the association between SL, social support (SS), flow experience (FE), and SA. A total of 435 older adults participating in air volleyball events were included in this study. The findings revealed that: (ⅰ) SL directly and positively influences on SS, FE, and SA; (ⅱ) SS is positively related to FE, and FE is positively associated with older adults' SA; (ⅲ) Both SS and FE fully mediate the relationship between SL and SA, with SS partially explaining this mediation through FE. This study builds upon prior research in this field and highlights the significance of SL for the SA among older adults. Future studies should further explore the underlying mechanisms linking serious sport experiences to successful elderly life.